Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1158/2326-6066.cir-18-0833
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of β-Adrenergic Receptors Improves CD8+ T-cell Priming and Cancer Vaccine Efficacy

Abstract: b-Adrenergic receptor (b-AR) signaling exerts protumoral effects by acting directly on tumor cells and angiogenesis. In addition, bAR expression on immune cells affects their ability to mount antitumor immune responses. However, how bAR signaling impinges antitumor immune responses is still unclear. Using a mouse model of vaccine-based immunotherapy, we showed that propranolol, a nonselective b-blocker, strongly improved the efficacy of an antitumor STxBE7 vaccine by enhancing the frequency of CD8 þ T lymphocy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 54 publications
(74 reference statements)
2
33
0
1
Order By: Relevance
“…15 They do not come singly but in pairs, signaling through ß2-AR negatively regulates CD8 + T cell's priming. 33 Interestingly, we also found a significantly decreased ratio of FoxP3 + in CD4 + T cells. The CD4 + FoxP3 + Treg cells are thought to play an important role in antitumor immune response.…”
Section: Articlesupporting
confidence: 50%
“…15 They do not come singly but in pairs, signaling through ß2-AR negatively regulates CD8 + T cell's priming. 33 Interestingly, we also found a significantly decreased ratio of FoxP3 + in CD4 + T cells. The CD4 + FoxP3 + Treg cells are thought to play an important role in antitumor immune response.…”
Section: Articlesupporting
confidence: 50%
“…Case‐control studies from the UK, the Netherlands and the United States could also not show beneficial effect in melanoma patients receiving ICI therapy 171–173 . A recent study in a murine melanoma model showed enhanced effect of vaccine in combination with β‐blockers due to a direct effect of β‐blockers on naïve CD8+ T cells which have high levels of β‐AR 174 . In contrast to mice, human memory CD8+ T cells express higher levels of β‐AR than naïve CD8+ T cells 175 .…”
Section: Increasing Effectiveness Of Tcr In Melanomamentioning
confidence: 99%
“…The studies by Xie et al (Xie et al, 2019), Montoya et al (Montoya et al, 2019), and Maiko et al (Sasaki et al, 2019) showed that BBs inhibited the occurrence and development of cancer by regulating gene expressions. Daher et al (Daher et al, 2019) and Inderberg et al (Inderberg and Wälchli, 2020) also found that BBs regulated the effect of inflammation on tumors. In general, BBs, such as ACEIs/ARBs, regulate their occurrence and development through multiple channels; nonetheless, more mechanisms will be discovered in the future.…”
Section: Anti-hypertensive Drugs Affect Cancer Progression Through Mumentioning
confidence: 93%